The Influence of Tensile Stress on Creep Distortion - W. Osipiuk (Engineering Transactions, 1991)
An experiment is presented concerning the process of creep in a plane state of stress under non-proportional loading by a torque and a tensile force. At a fixed value of the torque, the influence of a tensile force upon the shear deformation of non-steady creep process was analyzed. The PA4 aluminium alloys were tested. The plastic resistance function was used to describe the deformation. The concept of slip lines as proposed by Batdorf, Budiansky was used. The theoretical results derived comply with experimental data.